Unthought, or, A contribution to leadership scholarship from a Chinese perspective – based on François Jullien’s work : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Management at Massey University, Albany campus, New Zealand - Yue, Feng (Dennis) (Massey University, 2022)
This theoretical thesis is based on the work of French philosopher François Jullien. The thesis considers issues and challenges in existing leadership scholarship as an outcome of the Western cultural lens. Jullien’s work investigates Western and Chinese thinking traditions and recognises that the emergence of a cultural scholarship is heavily influenced by the ways the sensory world is categorised. The categorisation of reality on the basis of ‘being’ influences aspects of the sensory world a scholar is attentive to and created conditions for the emergence of Western scholarship. The Chinese ideographical language categorised the world on the basis of motion and produced a scholarship that is attentive to silent motions in the sensory world and not identifiable “being” and studies the propensity of things and not identity. By taking a Chinese perspective to reinvestigate Western thinking and vice versa, Jullien’s work makes a contribution by uncovering how separate cultural traditions contribute to each other by revealing insights that are unavailable from only one cultural scholarship (Jullien, 2014, 2015). Jullien calls the knowledge that emerges from between cultural thoughts unthought. This thesis aims to address the question of How can François Jullien’s work contribute to contemporary leadership studies? Following Jullien’s approach, I investigate leadership through a Chinese lens provided by Jullien’s work and uncover unthought in existing leadership scholarship by revealing insights about leadership from a Chinese perspective. This insight adds to leadership knowledge and provides alternative ways of approaching leadership through silent tendencies behind the emergence of identifiable aspects of leadership.
Keywords: Jullien, François, 1951-; Leadership; China; Civilization; Philosophy; 350707 Leadership